Investigations on spectroscopic characterizations, molecular docking, NBO, drug-Likeness, and ADME properties of 4H-1,2,4-triazol-4-amine by combined computational approach - Celik, Sibel; Yurdakul, Senay (European Journal of Chemistry, 2021)
In this study, the spectroscopic characterization, frontier molecular orbital analysis, and natural bond orbital analysis (NBO) analysis were executed to determine the movement of electrons within the molecule and the stability, and charge delocalization of the 4H-1,2,4-triazol-4-amine (4-AHT) through density functional theory (DFT) approach and B3LYP/6-311++G(d,p) level of theory. Surface plots of the hybrids’ Molecular Electrostatic Potential (MEP) revealed probable electrophilic and nucleophilic attacking sites. The discussed ligand were observed to be characterized by various spectral studies (FT-IR, UV-Vis). The calculated IR was found to be correlated with experimental values. The UV-Vis data of the molecule was used to analyze the visible absorption maximum (λmax) using the time-dependent DFT method. Since the principle of drug-likeness is usually used in combinatorial chemistry to minimize depletion in pharmacological investigations and growth, drug-likeness and ADME properties were calculated in this research to establish 4-AHT molecule bioavailability. Furthermore, molecular docking studies were carried out. Molecular docking analysis was performed for the title ligand inside the active site of the Epidermal Growth Factor Receptor (EGFR). The title compound’s anti-tumor activity against the cancer cell, in which EGFR is strongly expressed, prompted us to conduct molecular docking into the ATP binding site of EGFR to predict whether this molecule has an analogous binding mode to the EGFR inhibitors (PDB: ID: 1M17).